Evaluation of root dentin thickness and smear layer removal efficacy of two novel nickel titanium rotary instruments - An In Vitro cone-beam computed tomography and scanning electron microscopy study - Gangili Sparsha Reddy; Rajeswari Kalaiselvam; Arasappan Rajakumaran; Manigandan Kuzhanchinathan; Ram Sabarish; Arathi Ganesh (Wolters Kluwer Medknow Publications, 2021)
Objective: This study aimed to compare the two nickel-titanium (NiTi) instruments on root dentin thickness using cone-beam computed tomography (CBCT) and ability to remove the smear layer using scanning electron microscope (SEM). Materials and Methods: The effect of two NiTi rotary instruments such as XP Endo shaper and ProTaper Gold (PTG) in retaining adequate dentin thickness and debridement (i.e., removal of smear layer) was evaluated in vitro using CBCT and SEM. After cleaning and shaping of the root canal with adequate irrigation, the effect of two NiTi instrument systems at 3 mm (apical), 6 mm (middle), and 9 mm (coronal) levels on buccal, lingual, mesial, and distal aspects in terms of amount of dentin removal and smear layer removal was evaluated. The data were analyzed using student's unpaired t-test with a significance of P ≤ 0.05. Results: Both NiTi instrument systems had no statistically significant difference in amount of dentin removal at all three levels and on all four aspects. In smear layer removal, PTG had significantly better efficacy compared to XP Endo shaper at the coronal third of root canal. Conclusion: Instrumentation with XP Endo Shaper and PTG showed a similar amount of dentin removal. PTG has a significant effect on smear layer removal compared to XP Endo Shaper only at the coronal third of root canal.